(3QSGdI aj ebOeI GdhGLHs - (3GdNhGfSGQj, GdNhGfSGQj, MSjf Hf eMeO Hf GdMSjf GdNhGfSGQj, J (B1131(3g`s ((3RfLGf SGcjs)
(3ChdgG (B:s
(3ChdgG(B: (3GYde Cf bOeGA GdCUhdjjf CWdb GdNdGa aj Cf eG dG jJe GdhGLH EdG Hg hcGf ebOhQG agh hGLHs
(3BNQgG (B:s
(3BNQgG(B: (3HeYfi JMbjb GdGeJKGd HgG ef (B... (3hYOe ONhd GdeQGJ GdRGFOI aj GdGeKGd deG CTQfG Edjg aj gPg GdeSCdI aGdeSCdJGf YfOfG hGMOI(B. (3hGddg Gdehab hGdeYjfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI, L (B22: 67s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3CUhd Gdabgs